Reimplementation of the Connectivity Map with Accessibility Enhancements - Aricanli, Evren (Jihočeská univerzita, 2021)
The Connectivity Map (CMap) is a biomedical research tool which leverages modern biotechnology and bioinformatic methods to provide a platform for comparing the a subject gene expression profile against a library of drug-treatment gene expression profiles. This comparison allows for retrieval of drugs from the CMap's library which induce biological activity similar (or dissimilar) to a given subject expression profile -- thereby making it a tool which allows for the finding of repositionable drugs. Herein, a number of adaptations are proposed -- most focally being changes which would enhance the tool's accessibility (e.g. a simplified UI/workflow, expanded queryable gene identifiers). Using the R statistical computing environment and numerous libraries available through it, an adapted CMap tool was created from the publically-accessible CMap data, which housed the proposed adaptations. To evaluate success of the accessibility adaptations, the adapted CMap tool was focus tested on several participants -- which ultimately yielded great favor for the changes made, allowing them to be conclusively suggested for future iterations of the CMap.
Reimplementation of the Connectivity Map with Accessibility Enhancements
Keywords: Connectivity Map; Gene Expression Analysis; DNA microarrays; User Interface Accessibilty; Factor Analysis for Robust Microarray Summarization; Custom Microarray CDFs; Drug Repositioning; Connectivity Map; Gene Expression Analysis; DNA microarrays; User Interface Accessibilty; Factor Analysis for Robust Microarray Summarization; Custom Microarray CDFs; Drug Repositioning